The Relationships among Buyers’ Perceived Risk, Exhibitors’ Brand Equity, Purchase Postponement and Switching Intention-From the Perspectives of Perceived Risk Theory and Expectancy Theory - Hung, Chao-Chih; ., Che-Huei Lin (Information Management and Business Review, 2015)
This study explores the effects of buyers’ perceived risk on their purchase postponement and switching intention in an international industrial fair, as well as examines the moderating effect of exhibitors’ brand equity on the above relationships. This study uses the purposive sampling method to survey buyers of the famous International Woodworking Machine Fair in Hanover, Germany. Of the 200 surveys distributed, 105 valid questionnaires were returned, representing a response rate of 52.50%. Analytical results show that higher buyers’ perceived risk is associated with buyers’ higher purchase postponement, and stronger switching intention. Furthermore, when facing high-brand equity exhibitors’ products, if buyers perceive low risk of use, they are unlikely to delay purchase and switch suppliers; in contrast, if they perceive high risk of use, they are more likely to delay purchase and switch suppliers. Finally, when buyers face low-brand equity exhibitors’ products, if they perceive low risk of use, they will delay purchase and switch suppliers; in contrast, if they perceive high risk of use, they will tend not to delay purchase and switch suppliers.